ADAPTASI MASYARAKAT PESISIR TERHADAP PEMENUHAN KEBUTUHAN AIR DOMESTIK AKIBAT DAMPAK BANJIR ROB DI SEMARANG UTARA - , Widiyana Riasasi ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Tidal flood is frequent disaster that occurs in coastal area, i.e northern of Java coastal area. The disaster causes sea water infiltrating into fresh water in North Semarang Sub District, among others are in Panggung Lor, Panggung Kidul and Plombokan villages. Clear water scarcity leads to difficulty for the households to supply domestic water needs. The objectives of this research are (1) to identify the quality of water resources in tidal flood impacted area of North Semarang (2) to identify community adaptation to supply domestic water needs and (3) to identify government policy related to community adaptation to supply domestic water needs. This research uses descriptive quantitative and descriptive qualitative method. Descriptive quantitative method is conducted to identify water quality of groundwater based on conductivity value. Descriptive qualitative method is conducted by interviewing and in depth interviewing to community and key informants in order to identify community adaptation and government policy related to supplying water for domestic needs. The result shows quality of groundwater in research area is deficient for supplying domestic water needs. Conductivity average value of 18 samples of groundwater from unconfined aquifer is 10.000 Î¼S/cm - 15.000 Î¼S/cm, which indicates is brackish. Conductivity average value of 34 samples of groundwater from confined aquifer is 5.000 Î¼S/cm - 14.000 Î¼S/cm, which indicates is slightly brackish. Kinds of community adaptation to supply domestic water needs is using clean water from Drinking Water Local Company (PDAM), confined groundwater through artesian wells, water retailer, and also alternative source of refill water for consuming needs. Government plans regarding to supplying clean water are enhancing drain piping of PDAM and maximizing the potential of groundwater, surface water, and rain water by Rain Water Harvesting/RWH system.